New advances in exosome-based targeted drug delivery systems - Ferreira, Débora; Moreira, João Nuno; Rodrigues, Lígia R. (Critical reviews in oncology/hematology, 2022)
In recent years, various drug nano-delivery platforms have emerged to enhance drug effectiveness in cancer treatment. However, their successful translation to clinics have been hampered by unwanted side effects, as well as associated toxicity. Therefore, there is an imperative need for drug delivery vehicles capable of surpassing cellular barriers and also efficiently transfer therapeutic payloads to tumor cells. Exosomes, a class of small extracellular vesicles naturally released from all cells, have been exploited as a favorable delivery vehicle due to their natural role in intracellular communication and biocompatibility. In this review, information on exosome biogenesis, contents, forms of isolation and their natural functions is discussed, further complemented with the various successful methodologies for therapeutic payloads encapsulation, including distinct loading approaches. In addition, grafting of molecules to improve pharmacokinetics, tumor homing-ligands, as well as stimuli-responsive elements to enhance cell specificity are also debated. In the end, the current status of clinical-grade exosome-based therapies is outlined. [Display omitted] •Exosomes have been described as efficient delivery vehicles of a myriad of moieties.•Exosomes therapeutic potential can be greatly enhanced by engineering their content.•Multiple exosome surface engineering strategies have been developed.•Aptamers, peptides and antibodies are some of displayed molecules into exosomes.•Great efforts for the development of clinical-grade exosome-based therapies.